Profiling study of the Asnaf Incubator Program across Malaysian states - Abdul Razak, Abdul Qayuum; P. Rameli, Mohd Faizal; Che Man, Norajila; Mohd Fadzil, Muhammad Faidz; Mohamed @ Haji Daud, Norizah; Amin, Suhaida (2023)
The quality of life of the Malaysian population stands as a primary concern in the construction of a progressive and competitive Malaysian nation. In parallel, the asnaf community receives its share of benefits from this advancement. The asnaf populace is of paramount importance in this endeavour as they constitute a portion of the B40 socioeconomic group. To ameliorate their poverty conditions, various programs have been formulated and executed by the state-level zakat institutions. These programs encompass the provision of business resources, capital support, training initiatives, and other forms of early-stage assistance aimed at enabling them to embark on their respective entrepreneurial endeavours. Among the offerings provided by state zakat centres are entrepreneurship courses held in several states such as Melaka, Selangor, Johor, among others. Therefore, this research endeavour seeks to dissect the profiles of asnaf zakat participants engaged in agricultural entrepreneurship incubator programs. The research methodology adopted employs a quantitative approach through a questionnaire instrument designed to scrutinize the participants' backgrounds. The collected data will be subjected to analysis utilizing the Statistical Package for Social Science (SPSS) software. The sample selection (N=62) were predicated upon purposive sampling, concentrating on individuals who are actively engaged in these programs. The result were presented in frequency tables to show the respondents demographic information. The findings reveal that the participants possess educational qualifications extending up to the Malaysian Higher School Certificate (STPM) level and hail from economically disadvantaged households. Asnaf are burdened with a considerable number of dependents within their families. Further investigations to assess the effectiveness of these programs on the participants are imperative, as they enable zakat institutions to evaluate and strategize for future initiatives. The suggested implications involve creating scholarships, job opportunities, financial aid, and community support to help these individuals access education and improve their quality of life. These strategies are aimed at addressing the challenges faced by this group. The research shows that participants have educational qualifications up to the STPM level and come from economically disadvantaged households.